Association of arterial hypertension and cognitive impairment in euthymic bipolar disorder - Hubenak, Jan; Tuma, Ivan; Bazant, Jan (Neuro endocrinology letters, 2015)
OBJECTIVES: Cognitive impairment in euthymic phase of bipolar disorder has been documented in many studies. Several factors may contribute to such impairment, e.g. sedative medication, thyreopathy. Metabolic syndrome with its components represents another frequent condition found in bipolar disorder exerting probably adverse impact on cognition. Since it is treatable factor and current literature suggests possible connection with cognitive dysfunction, we aimed to explore such associations to identify promising targets of complex treatment. METHODS: Forty euthymic bipolar patients have been enrolled. Their body and metabolic parameters were measured. Medical history data were collected. Cognition was evaluated using battery of tests. Neuropsychological performance was transformed into neurocognitive composite score. Cognition of subjects was compared dichotomously according to presence or absence of pathological body and metabolic parameters. Correlations of selected parameters and composite score were done. RESULTS: Low neurocognitive score was found in presence of hypertension, metabolic syndrome, abdominal obesity and hyperglycemia. Only connection of hypertension and cognitive score reached sufficient statistical power. Patients presenting hypertension performed worse in all tested domains of cognition when compared with normal blood pressure group. Subjects using lithium performed substantially worse in cognitive tests. However, in comparison with anticonvulsant group, lithium users had markedly longer disorder history as well as longer duration of thymoprofylaxis. No significant correlation of HDRS score, insulinemia or HOMA-IR was found. CONCLUSION: Despite relatively small sample size, noticeable association of hypertension and cognitive impairment was revealed. This might indicate possible way of enhancing cognition in bipolar disorder by treating elevated blood pressure.
Keywords: dospělí; Bipolar Disorder; hypertenze; Female; bipolární porucha; Adult; kognitivní poruchy; ženské pohlaví; komorbidita; lidé; Comorbidity; Cognition Disorders; Hypertension; Male; Aged; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Humans